Consumption During Retirement: The Missing Link in the Life Cycle - Hamermesh, Daniel S. (The Review of Economics and Statistics, 1984)
This study presents the first evidence on the relation of consumption to lifetime wealth, based on data from the 1973 and 1975 Retirement History Survey that have been linked to Social Security earnings records.